Sobre mulheres, formas e revoluções: da personagem dramatúrgica e da metaficção historiográfica no drama moderno contemporâneo de Paulo Vieira - análise e interpretação de Anayde e Mercedes - Batista, Fernanda Félix da Costa (2025)
This is a study of modern and contemporary drama through the analysis and interpretation of the plays Anayde and Mercedes, which are part of the dramaturgy of the author from Paraíba, Paulo Vieira. Both plays are similar in that they feature female protagonists and historical themes that revisit two important moments in Brazilian history: the 1930 Revolution and the Military Dictatorship. The presence of these themes points to the possibilities of modern and contemporary drama, given the emergence of epic-narrative and lyrical elements within the dramatic form. The research focuses on the presence of different poetics and temporalities that allow the representation of subjects and themes that were once separated from absolute drama, seen from a closed and ahistorical perspective. The studies by Peter Szondi and Jean-Pierre Sarrazac are the theoretical and critical bases of this research and reveal the dialectical relationship between form and content, through which the form of drama comes to be conceived as historically determined, which corroborates the opening of the form to the countless possibilities of formalization. Thus, the historical theme emerges in the playwright's texts through the predominance of epic-narrative elements that are evidenced through discursive action. In Anayde, the representation of the love story between the protagonists reveals the context in which they are inserted, since, due to the inclement weather of the political context they are experiencing, they are led to a tragic destiny that prevents them from fully living their desires. In Mercedes, the author explores other possibilities of the modern form of drama and, through a circular action, promotes a break with the present and linear time-space of the drama, by formalizing an action that is constantly returning to the characters' past. The historical context expressively represented in both texts allows a critical look at important events in history, observed from the perspective of the present time, fostering a critical look at the historiographical discourse. The discursive construction around the critical reworking of legitimized narratives points to the philosophy of postmodernism that is present in fiction through what Linda Hutcheon (1991) called historiographical metafiction, when thinking about the forms of the novel that recover historical events. Given this scenario, we propose a study around the relations between History and Literature in contemporary times, considering the possibility that in Paulo Vieira's dramaturgy there is a formalization of historiographical metafiction under the molds of modern and contemporary drama, which points to a critical awareness of the playwright around his work and the theoretical-critical discourses around fiction, in general, and drama, in particular.